(untitled) (Research, Society and Development, 2023)
Objective: to investigate the existence of an application that cognitively assists elderly people with mild dementia. Method: we sought to analyze existing studies on the use of mobile applications to promote the cognitive development of elderly people who are in the initial dementia process. Thus, this study consists of a survey in the format of a Systematic Literature Review (SLR) that followed the guidelines of the PRISMA protocol. The searches were carried out in March 2022, in the electronic databases “LILACS”, “Scopus”, “SciELO”, “PEPSIC”, “PUBMED”, “Web of Science” and “PKP (Publik Knowledge Project)”. Result: the analysis found that there are some mobile applications aimed at this purpose, but many are under development or need improvements. Conclusion: it is necessary to both advance the ideas of existing mobile applications and create mobile applications that really help in the daily lives of elderly people in the dementia stage, providing a better quality of life for them and daily cognitive stimulation.